The Effect of a Higher Bias Gas Flow on Imposed T-Piece Resistance and Breathing in Preterm Infants at Birth - Kuypers, Kristel L. A. M.; Willemsen, Lieve A.; Cramer, Sophie J. E.; Kashyap, Aidan J.; Drevhammar, Thomas; Hooper, Stuart B.; te Pas, Arjan B. (Frontiers in Pediatrics, 2022)
Objective The resistance created by the PEEP-valve of a T-piece resuscitator is bias gas flow dependent and might affect breathing in preterm infants. In this study we investigated the effect of a higher bias gas flow on the imposed inspiratory and expiratory T-piece resistance and expiratory breaking manoeuvres (EBM) in preterm infants during spontaneous breathing on CPAP at birth. Methods In a retrospective pre-post implementation study of preterm infants < 32 weeks gestation, who were stabilised with a T-piece resuscitator, a bias gas flow of 12 L/min was compared to 8 L/min. All spontaneous breaths on CPAP within the first 10 minutes of starting respiratory support were analysed on a breath-by-breath basis to determine the breathing pattern of each breath and to calculate the imposed inspiratory and expiratory T-piece resistance (Ri, Re), flow rates and tidal volume. Results In total, 54 infants were included (bias gas flow 12 L/min: n=27, 8 L/min: n=27) with a median GA of 29+6 (28+4-30+3) and 28+5 (25+6-30+3), respectively (p=0.182). Ri and Re were significantly lower in the 12 L/min compared to 8 L/min bias flow group (Ri: 29.6 (26.1-33.6) vs 46.4 (43.0-54.1) cm H2O/L/s, p<0.001; Re: 32.0 (30.0-35.1) vs 48.0 (46.3-53.9) cm H2O/L/s, p<0.001), while the incidence of EBM (77% (53-88) vs 77% (58-90), p=0.586) was similar. Conclusion During stabilisation of preterm infants at birth with a T-piece resuscitator, the use of a higher bias gas flow reduced both the imposed inspiratory and expiratory T-piece resistance for the infant, but this did not influence the incidence of EBMs.